El Niño-Southern oscillation impacts on agriculture and the national economy - Koo, Jawoo; Thurlow, James; Xie, Hua; Robertson, Richard D.; Azzarri, Carlo; Kwon, Ho Young; Haile, Beliyou (International Food Policy Research Institute, 2019)
A range of interventions have been identified that, if implemented, could help mitigate the adverse effects of climate shocks, such as El Niño- Southern Oscillation (ENSO) events, on the Ethiopian economy and the food security of its population. As outlined in Chapter 2, these interventions include, among others, on-farm investments in technology and irrigation infrastructure, investments in roads and grain storage facilities to expand and stabilize food markets, and social transfers to provide households with a cushion against immediate crises and opportunities for longer-term recovery. However, resource constraints and competing interests mean that there are sometimes trade-offs associated with pursuing policies aimed at building resilience to climate shocks versus policies aimed at achieving other development objectives. Therefore, to motivate resilience-building policies, it is necessary to assess the costs of inaction; to measure policy effectiveness using recognized outcome indicators; and to identify synergies between, say, resilience and development interventions and objectives.